AN AUDIT OF LOBECTOMY FOR PULMONARY DISEASE AT LADY READING HOSPITAL, PESHAWAR - Nadeem, Asif; Bilal, Amir; Jan, Sharifullah (Journal of Ayub Medical College Abbottabad, 2003)
Background: The present study was designed to provide data on the role of elective open lobectomies in the treatment of benign and malignant pulmonary diseases in our setting. Methods: An audit of patients’ records over a two-year period was performed to collect relevant data at the Cardio Thoracic Unit of the Lady Reading Hospital Peshawar Pakistan. Results: A total of 55 lobectomies were performed from January 1999 to December 2000, including 34 males and 21 females. The mean age of patients was 31.23 ± 14.95 years, with only 7 (12.7%) cases above 50 years of age. Benign pulmonary conditions, particularly chronic lung infections were the major indication for lobectomies (50/55, 90.9%), while lung cancers accounted for only 5/55 (9.1%) of lobectomies. Bronchiectasis was the leading indication with 28 (50.9%) lobectomy cases. Most patients (37/55, 67.3%) had uneventful postoperative recovery, while 18/55 (32.7%) developed some sort of complication. The most common postoperative complication was infection (wound infection and empyema) accounting for 8 patients (14.6%), followed by air leak (5/55, 9.1%). Mortality was low, with only 2 deaths (3.6%). Conclusion: Elective open lobectomy is a safe procedure in our setting with significant benefits for patients and acceptable morbidity and mortality. Key Words: Lobectomy, Chronic Lung Infection, VATS, Air Leak, Bronchiectasis.